Peran Kader dalam Meningkatkan Keberhasilan Program Pengobatan Pencegahan dengan Isoniazid (PP INH) pada di Kabupaten Jember - Heppy Martin Susetyowati; Farida Wahyu Ningtyias; Aris Prasetyo (Multidisciplinary Journal, 2018)
Tuberculosis (TB) becomes health problem in the world. Toddlers who interact with TB sufferers are at high risk for infected than adults, it is about 50-60% on the level of infection. Related to prevention of tuberculosis is needed through preventive treatment with isoniazid (PP INH) to healthy children aged <5 years who are interacting with TB patients. Based on Tanggul Health Center data, there are 37 toddlers who have received INH PP by involving health care providers, empowering cadres and the communities. However, This research aims to analyze the role of cadres such as the role of monitors. This research uses qualitative methods and case study approach. Besides, there are 5 main informants who has recruited purposively. The data are collected from in-depth interviews and analyzed through thematic content analysis. The results of this research shows that not all of TB cadres played their role as supervisors of swallowing medicines. This is because the distance of patients' home which made it difficult the cadres for coming to the patients’ home. Furthermore, the informant uses some method such as reminded the family to provide treatment using telepone (HP), and made their own notes about the specific problems of TB in their area where the cadre was assigned. The efforts to increase the compliance of PP INH treatment is optimized in providing information to the community both in the form of lectures or practices, giving support, and facilitating during the PP INH treatment process. Keywords: Role, TB Cadre and INH PP